Preventing bank runs - David Andolfatto; Ed Nosal; Bruno Sultanum (Federal Reserve Bank of Chicago, 2014)
Diamond and Dybvig (1983) is commonly understood as providing a formal rationale for the existence of bank-run equilibria. It has never been clear, however, whether bank-run equilibria in this framework are a natural byproduct of the economic environment or an artifact of suboptimal contractual arrangements. In the class of direct mechanisms, Peck and Shell (2003) demonstrate that bank-run equilibria can exist under an optimal contractual arrangement. The difficulty of preventing runs within this class of mechanism is that banks cannot identify whether withdrawals are being driven by psychology or by fundamentals. Our solution to this problem is an indirect mechanism with the following two properties. First, it provides depositors an incentive to communicate whether they believe a run is on or not. Second, the mechanism threatens a suspension of convertibility conditional on what is revealed in these communications. Together, these two properties can eliminate the prospect of bank-run equilibria in the Diamond-Dybvig environment.
Keywords: D82; E58; G21; 330; bank runs; optimal deposit contract; financial fragility